'Urban Safaris': Looting, Consumption and Exclusion in London 2011. (November 2013) - Casey, Emma
This paper examines the prevalence and relevance of looting for understanding the 2011 English riots. It begins by distinguishing these riots from previous British riots by arguing that although looting is by no means a new phenomena looting nevertheless became central to discussions, interpretations and recollections of the riots. The paper will explore public and media responses to the looting and will focus on the uses of looting as a means of identifying a feral underclass of people seen to be morally and culturally separate from mainstream society. By unpicking the relationships between looting and what currently stands for 'consumer culture', the paper will argue that looting is seen as the lowest common denominator of mob behaviour since its focus is deemed to be entirely apolitical. The paper will look towards current understandings of consumer culture to try to make sense of the looting. It will argue that whilst there is now a good deal of literature exploring the relationships between judgments of taste and the reproduction of existing class structures and barriers, there is virtually nothing examining the relationships between consumption and social exclusion. I will argue in this paper that exclusion is crucial in providing a comprehensive understanding of the looting. In particular, I suggest that Bourdieusian accounts of the effects of popular expressions of disgust at the looters can offer only a partial understanding of the looting, since they do not explain the strength of desire for consumer goods. In order to address this, the paper expands on cultural capital discourses by incorporating the concept of 'emotional capital' into the analysis. The paper concludes by arguing that we should not be surprised by the widespread looting that took place in August 2011 given that advanced consumer society is characterised by common feelings and emotions and that many of the looters were not part of the original riots but opportunists who took advantage of the lack of police presence.